Product Quality, Product Design, and Online Customer Reviews as Determinants of Generation Z Purchase Decisions on Tiktok Shop: Evidence From Mossdoom Consumers in Denpasar - Kadek Ayu Candradewi; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
This study aims to examine the influence of product quality, product design, and online customer reviews on Generation Z’s purchasing decisions regarding Mossdoom brand bags in Denpasar via TikTok Shop. This study employs a quantitative approach using an associative method, with the population consisting of Generation Z individuals in Denpasar who have purchased Mossdoom products on TikTok Shop, while the sample was selected based on respondent criteria. Primary data was collected through a questionnaire and analyzed to understand the simultaneous and partial effects among the variables. The analysis results demonstrate that product quality has a significant positive effect on purchase decisions, product design has a significant positive effect on purchase decisions, and online customer reviews have a significant positive effect on purchase decisions. Simultaneously, these three variables significantly contributed to the purchase decision by 0.738 or 73.8%, suggesting that better quality, trend-aligned design, and convincing reviews will drive consumer purchasing decisions.